Political Violence as a Time That is Past? Engaging With Non-Participation in Transitional Justice in Cambodia. (October 2019) - Bernath, Julie
Transitional justice scholarship has increasingly focused on participation to critically reflect upon the legitimacy and transformative potential of transitional justice. This article addresses these issues yet through a different vantage point: that of non-participation. It focuses on the case study of the Khmer Rouge Tribunal and a particular set of actors: those who continue to face political violence in Cambodia today. Thereby, it engages with the perspectives of those often overlooked in transitional justice for having opted out of the process, but also for putting forward justice claims that exceed the mandate of established transitional justice institutions. This article draws from qualitative fieldwork conducted in Cambodia between 2013 and 2016. It demonstrates the epistemic value of engaging with non-participation in transitional justice. It argues that non-participation in judicial transitional justice processes is inherently linked to the ways in which ordinary citizens experience and understand the law in their everyday life. It further highlights continuities in subjective experiences of political violence, which question discourses that political violence is a time that is past in Cambodia.